Alunas migrantes venezuelanas: experiências de escolarização e convívio (Esteio/RS – 2023) - Azambuja, Caroline Carlet (Universidade do Vale do Rio dos Sinos, 2024)
This research emerges from the need to know how migrant teenagers feel at the municipal school in the city of Esteio and also connects the experiences of meaning of the group of students with everyday practices in the school environment. This study is inserted in two fields of knowledge, education and migration, and makes up a contemporary social phenomenon, which is the school insertion of second generations of migrants in Brazilian public schools. During the research, we analyzed national legislation involving arrival, legal and social guidelines, as well as the inclusion of children and adolescents from migrant families in schools. The study was constructed using the comprehensive interview methodology and was produced based on the speeches of three participants of Venezuelan origin, field observations and the use of the field notebook. The results found are related, above all, to two main axes, experience and everyday practices. From an education perspective for migrants, progress has already been made, however, there are still many sections and interfaces that must be researched and systematized. Another point worked on is the network of sociability, which is involved in key aspects involving culture and gender.
Keywords: Migração; Experiência; Práticas cotidianas; Educação; Education; Migration; Everyday practices; Experience; ACCNPQ::Ciências Humanas::Educação